The method for analysis and optimization of the e,X-beam path of electron linac-based radiation installations - Dovbnya, A.N.; Dovbnya, N.A.; Nikiforov, V.I.; Uvarov, V.L. (Вопросы атомной науки и техники, 2006)
A method is proposed for numerical analysis of radiation characteristics of output devices of the electron linac.
The method enables an optimum arrangement of the objects irradiated in the field of electron radiation and
bremsstrahlung. Results are reported from the analysis of equipment location at the exit of one of the NSC KIPT
electron linacs. The results were obtained by the mathematical simulation method with the use of the PENELOPE
code system. Предложен метод численного анализа радиационных характеристик выходных устройств ускорителя электронов. Метод позволяет оптимально расположить объекты, облучаемые в поле электронного и тормозного излучения. Приводятся результаты анализа размещения оборудования на выходе одного из линейных ускорителей ННЦ ХФТИ. Результаты получены методом математического моделирования с помощью программной системы PENELOPE. Пропонується метод чисельного аналізу радіаційних характеристик вихідних пристроїв прискорювача
електронів. Метод дозволяє оптимально розмістити об’єкти, що опромінюються в полі електронного і
гальмівного випромінювань. Приводяться результати аналізу розміщення устаткування на виході одного з
лінійних прискорювачів ННЦ ХФТІ. Результати одержані методом математичного моделювання за
допомогою програмної системи PENELOPE.